Hybrid membrane-cryogenic CO2 capture technologies: A mini-review - Sreenath, S.; Sam, Ashish Alex (Frontiers in Energy Research, 2023)
The use of membranes to capture CO2 is a proven carbon capture technique. Gas separation membranes enhance the mole fraction of CO2 in the feed gas. The membrane separation technique is low-cost because of its compact size, excellent energy efficiency, minimum environmental effect, simplicity of scale-up, fewer moving parts, moderate energy consumption, and ease of handling. Hybrid membrane cryogenic (HMC) and low-temperature membrane cryogenic (LTMC) are hybrid capture systems that combine the advantages of membrane and cryogenic techniques. In the HMC process, the flue gas is first pre-treated by the membrane process for CO2 enrichment and the cryogenic process to capture the CO2. In the LTMC process, low-temperature membrane units increase flue gas CO2 concentration to 50%–75%, and a cryogenic process liquefies the rich CO2 stream. Permeability and selectivity are the crucial parameters of the membrane which determine the CO2 purity and recovery of capture. Most polymeric membranes have a trade-off of CO2/N2 selectivity (αCO2/N2) and CO2 permeability (PCO2). The operating temperatures also impact membrane performance. An anti-trade-off effect was observed upon cooling down by increasing PCO2 and αCO2/N2. With increased PCO2 and αCO2/N2, sub-ambient temperature-based membrane cryogenic CO2 capture techniques will lower power consumption and energy cost for CO2 capture (CC). This review analyses the costs and energy requirements of various HMC and LTMC configurations for CO2 capture. The study also examines the features of the different membranes used and the effect of operating and membrane parameters on the process performance.